A Longitudinal Examination of the Directional Effects between Relationship Quality and Well-Being for a National Sample of U.S. Men and Women. - Roberson, Patricia N. E.; Lenger, Katherine A.; Norona, Jerika C.; Olmstead, Spencer B. (Sex Roles, 2018)
The interaction between relationship quality and individual well-being has commonly been examined using a negative conceptualization of these constructs (e.g., relationship aggression and depression, respectively). The present study examines the direction of association between individual well-being and relationship quality. Specifically, we examined if this direction differed based on positive and negative conceptualizations of individual (i.e., life satisfaction and depression) and relationship (i.e., relationship satisfaction and conflict) well-being and how this differed for men and women. Using a series of cross-lagged path analyses across three time points, we found that relationship satisfaction and life satisfaction were mutually influential over time, but life satisfaction was only predictive of later conflict. Further, depression predicted both later relationship conflict and relationship satisfaction. Regarding gender differences, life satisfaction and relationship satisfaction exhibited a cyclical relationship for men but not for women. For women, but not men, depression was related to later relationship satisfaction. Taken together, these results suggest that nuances exist in the association between relationship quality and individual well-being depending on the conceptualization of the construct (negative vs. positive) and gender. More specifically, it appears that life satisfaction, or positive conceptualizations of well-being, may be more relevant to men's relationship quality whereas depression, or negative conceptualizations of well-being, may be more relevant to women's relationship quality. Clinical implications and directions for future research are discussed.